Peace, conflict and violence in Ecuador, 2019 - Sandra Maurera C. (Revista de Cultura de Paz, 2019)
This documentary and qualitative research, based on the theories and concepts established by Johan Galtung (1964, 1969 and 2003), has two objectives. In first place, to reveal the basic ideas of peace, conflict and violence that were build by the online written Ecuadorian (El Universo, El Diario, El Comercio, etc.) and International press (France24) during the events that occurred in October of 2019, after the 883 decree was known. Once this review is concluded, the second stipulated objective is to propose some guidelines that could be carried out in the UTPL classrooms. This review is carried out in several Ecuadorian institutions selected from the notions raised by Berger and Luckmann (2003 [1968]): University, Church, Civil Society, opposition, etc. The study shows that any collegiate career could support peace and conflict from a positive perspective; but it also proposes that the UNESCO subject of Culture and Education for Peace of the UTPL extend its work through classes -Ethical and moral, for example - administered by scientific, technical and humanistic careers.